A Human Rights-Based Approach Study to Address Child Marriage in the Dayak Kanayat’n Indigenous Community in Mempawah Regency - Dewi, Norvirta; Selsa Rizki Agustin Sakila; Suwartikarin, Cremona; Hazilina, Hazilina (JUSTITIA JURNAL HUKUM, 2026)
Child marriage constitutes a persistent violation of children’s rights, often sustained by the interaction of customary norms, economic pressures, and limited access to education. This research examines the practice of child marriage in Toho Subdistrict, Mempawah Regency, with particular attention to the influence of Dayak Kanayat’n customary norms. The study aims to analyze how customary law shapes child marriage practices, assess the extent to which human rights principles can be integrated into these norms, and formulate strategies to harmonize a human rights-based approach with respect for cultural values. This research employs an empirical legal research method with a socio-legal approach. The findings reveal that child marriage is commonly justified through customary interpretations related to family honor, social harmony, and economic considerations. Nevertheless, the study finds that human rights principles, especially those concerning children’s rights, are not fundamentally incompatible with customary norms but are often insufficiently understood and institutionalized within local practices. The research identifies the potential for harmonization through culturally sensitive advocacy, reinterpretation of customary values, and the active involvement of customary leaders as key agents of change. this study proposes a collaborative model involving customary institutions, local government, and civil society to promote gradual cultural transformation while ensuring effective protection of children’s rights.